Fragmentation considered harmful. - Kent, C.A (Computer communication review.)
Internetworks can be built from many different kinds of networks, with varying limits on maximum packet size. Throughput is usually maximized when the largest possible packet is sent; unfortunately, some routes can carry only very small packets. The IP protocol allows a gateway to fragment a packet if it is too large to be transmitted. Fragmentation is at best a necessary evil; it can lead to poor performance or complete communication failure. There are a variety of ways to reduce the likelihood of fragmentation; some can be incorporated into existing IP implementations without changes in protocol specifications. Others require new protocols, or modifications to existing protocols.